2004
DOI: 10.1152/japplphysiol.01355.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus-induced sleep responses in mice with targeted disruptions in neuronal or inducible nitric oxide synthases

Abstract: Influenza viral infection induces increases in non-rapid eye movement sleep and decreases in rapid eye movement sleep in normal mice. An array of cytokines is produced during the infection, and some of them, such as IL-1beta and TNF-alpha, are well-defined somnogenic substances. It is suggested that nitric oxide (NO) may mediate the sleep-promoting effects of these cytokines. In this study, we use mice with targeted disruptions of either the neuronal NO synthase (nNOS) or the inducible NO synthase (iNOS) gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…However, SWS delta power, a measure of SWA, was significantly greater in nNOS KO mice than in their wild type controls during all phases of the circadian cycle (Chen et al, 2003). The same authors also found that influenza-induced elevation of time spent in SWS was attenuated in nNOS-deficient mice (Chen et al, 2004). Thus, while nNOS may in fact suppress sleep SWA under baseline conditions, it appears to facilitate sleep in the context of viral infection.…”
Section: Neuronal No As a Sleep-inducing Factor: Local Regulation Of mentioning
confidence: 89%
“…However, SWS delta power, a measure of SWA, was significantly greater in nNOS KO mice than in their wild type controls during all phases of the circadian cycle (Chen et al, 2003). The same authors also found that influenza-induced elevation of time spent in SWS was attenuated in nNOS-deficient mice (Chen et al, 2004). Thus, while nNOS may in fact suppress sleep SWA under baseline conditions, it appears to facilitate sleep in the context of viral infection.…”
Section: Neuronal No As a Sleep-inducing Factor: Local Regulation Of mentioning
confidence: 89%
“…A mouse-adapted strain of influenza, H1N1 A/Puerto Rico/8/34 H1N1 (PR8) (lot#3X010621) suspended in pyrogen-free allantoic fluid (Specific Pathogen-Free Avian Supply, North Franklin, CT) was purified by sucrose-gradient sedimentation by ultracentrifugation as previously described (18). The virus was diluted to a protein concentration of 200 µg/mL, aliquoted, frozen on dry ice, and stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the purified virus tested negative for mycoplasma and acholeplasma contamination by nested PCR (nPCR) (American Type Culture Collection, Manassas, VA) as previously described (19). In Madin-Darby canine kidney (MDCK) cells, viral titrations were assessed and expressed as median tissue culture infectious doses (TCID 50 ) as previously described (18) . The starting titer of purified PR8 virus was 5× 10 4 TCID 50 /µL.…”
Section: Methodsmentioning
confidence: 99%
“…About 10,000-fold more X-31 virus is required to kill mice in the same time-frame as PR8, largely due to the retention of glycosylated surface proteins on X-31 that are targeted by circulating host lectins (Reading et al, 1997). The X-31 virus grown in specific pathogen-free chick embryos was purified and tested for possible contaminants as previously described (Chen et al, 2004). Viral titrations were performed in Madin-Darby canine kidney cells as previously described (Chen et al, 2004) and expressed as median tissue culture infectious doses (TCID 50 ).…”
Section: Methodsmentioning
confidence: 99%